2012
DOI: 10.4067/s0718-58392012000400014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding Acacia saligna (Labill.) H.L. Wendl. on goats stabled during late pregnancy and lactation

Abstract: Acacia saligna (Labill.) H.L. Wendl. forage is an alternative feed supply for goats during dry periods It was used as feed during pregnancy and lactation to evaluate production response and some blood parameters. Six animals in each group were fed with 0, 25, 50, 75, and 100% of acacia as alfalfa (Medicago sativa L.) hay replacement in a completely randomized design. Forage chemical analysis was done to calculate nutrient intake. Blood samples were analyzed for albumin, urea N, globulin, total protein, Ca, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…However, it was observed that pregnant ewes fed 40% ALH diet recorded the same total body weight gain and ADG that were recorded by those fed control, and slightly lower than those fed 40% ALH diet. The present results are in good agreement with those of Meneses, et al, (2012) who reported that when goats in late pregnancy fed alfalfa hay diet (control) and replacement Acacia hay instead of alfalfa hay by 25, 50, 75 and 100% diets, the body weight changes did not show a significant differences (P0>0.05) among treatments . They illustrated that CP and ME intake during the experimental treatments was probably not sufficient to establish significant responses during the last third period of pregnancy.…”
Section: Pregnant Ewes Body Weight Changes Daily Gain and Body Weighsupporting
confidence: 93%
See 2 more Smart Citations
“…However, it was observed that pregnant ewes fed 40% ALH diet recorded the same total body weight gain and ADG that were recorded by those fed control, and slightly lower than those fed 40% ALH diet. The present results are in good agreement with those of Meneses, et al, (2012) who reported that when goats in late pregnancy fed alfalfa hay diet (control) and replacement Acacia hay instead of alfalfa hay by 25, 50, 75 and 100% diets, the body weight changes did not show a significant differences (P0>0.05) among treatments . They illustrated that CP and ME intake during the experimental treatments was probably not sufficient to establish significant responses during the last third period of pregnancy.…”
Section: Pregnant Ewes Body Weight Changes Daily Gain and Body Weighsupporting
confidence: 93%
“…The present results of DM intake are in a good agreement with those obtained by Meneses, et al (2012). They studied the effect of using Acacia saligna (Labill.)…”
Section: Feed Intakesupporting
confidence: 91%
See 1 more Smart Citation
“…At the same trend, Meneses et al, (2012) fed lactating ewes on 0, 25, 50, 75, and 100% of Acacia as alfalfa (Medicago sativa L.) hay replacement in a completely randomized design. They found that DM, CP, and ME intake were increased (P < 0.01) in the lactation stage over the control with a high percentage of Acacia in the diet, which differed from the results during pregnancy.…”
Section: Feed Intake and Nutritive Valuementioning
confidence: 99%
“…On the contrary, Meneses et al (2012) used goats on 0, 25, 50, 75, and 100% of Acacia as alfalfa (Medicago sativa L.) hay replacement. The milk production for 0 and 25% treatments were the same but different from those for the other treatments, which were 160.…”
Section: Milk Yieldmentioning
confidence: 99%